Discriminação com três tipos de contingências supressivas: extinção, punição e extinção + punição - FARIAS, Danielle Chaves de (Universidade Federal do Pará, 2014)
In studies on stimulus control is predominantly used reinforcement in SD and Extinction in SΔ to establish a simple discrimination. Few studies used Punishment in SΔ to establish such a differential responding, however, most of those produced faster learning than traditionally achieved with extinction only. When this type of procedure was used, in general, the electric shock was used as punishment. Carvalho Neto and Cols. have experimented a hot air blast (HAB) as an aversive alternative stimulus and so far successed in suppressive contexts (contingent and non contingent presentation) and negative reinforcement (escape and avoidance). Carvalho Neto and Farias (2006) and Carvalho Neto and Costa (2008) tested the HAB as suppressor in SΔ seeking to produce a light/dark discrimination and punitive contingencies in these studies were more effective than the traditional. However, some methodological problems were identified in these studies that limited their conclusions. This study sought to control some of these variables, in particular, the passage of fixed time and type of scheme in place. Six male rats were divided into three conditions: Extinction, Punishment and Extinction+Punishment. An operant conditioning box adapted to HAB was used. The procedure for the three conditions was the same, except for the sessions of Discrimination Training (reinforcement in SD for all conditions and during SΔ: Extinction for the extinction condition, Punishment for the Punishment condition and Punishment+Extinction for Punishment+Extinction condition). The subjects of the conditionsin wich the punishment was used showed a discriminated responding while the subjects assigned to Extinction condition failed to produce this responding pointing that the use of aversive control was more efficient that the traditional procedure.